TEACHING ENGLISH FOR TOURISM IN BALI BASED ON LOCAL CULTURE: WHAT DO STUDENTS NEED? - Rima Andriani Sari (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
The demands of English speaking workers in tourism and travel industry in Bali is increasing and this leads to the increase of the number of vocational learning and training for Tourism. However, more attention is given to the source culture (English culture) rather than the target culture (local culture) in most teaching materials. English for Tourism (under the  course name English for Tour and Travel), an ESP in English Education Department Undiksha,  has the same problem. Students learn English to talk to visitors who come to their country, but they are not expected to travel to target countries or to learn about target cultures while the textbook used focus more on the target culture. A new design of teaching material based on local culture is then needed. This paper reports an on-going project which aims at designing teaching materials based on local culture for English Tour and Travel. The development is carried out in three major stages. The paper draws on the data of the first stage that has been completed, and discusses the needs of the the EED students learning English for Tour and Travel based on local culture in several aspects: tourism topics, language functions, language skills, and local culture. It highlights the learners’ needs in the eyes of students, tourism practitioners and lecturers and discusses the implications of these on the design of the English for Tour and Travel teaching material.